The Impact of Hypoxemia on the Development of Retinopathy of Prematurity in Infants Less Than 29 Weeks of Gestation - Afshar, Narges; Baier, Ronald J.; Tagin, Mohamed; Cabo, Cecilia de; Minski, John; Elsayed, Yasser N. (American Journal of Perinatology, 2018)
Objective To study the impact of cumulative exposure to hypoxemia on the development of retinopathy of prematurity (ROP) in preterm infants less than 29 weeks' gestation.Study Design This is a retrospective analysis of the effect of cumulative exposure to hypoxemia during the first 10 weeks of life in preterm infants <29 weeks' gestation. Cumulative time spent at various levels of oxygen saturation was calculated by converting the daily percentage of time to minutes per day. Cumulative exposure to hypoxemia (cT<80 or oxygen saturation <80%) was calculated weekly and compared between outcomes. The primary outcome was the development of ROP requiring treatment.Results Cumulative hypoxemia exposure was significantly associated with ROP requiring treatment. When adjusted for other neonatal morbidities, only gestation was consistently associated with ROP requiring treatment.Conclusion Cumulative exposure to hypoxemia in the first few weeks was not associated with ROP or treatment of ROP after adjustment for confounders.
Keywords: hypoxemia; retinopathy of prematurity; oxygen histogram